Concomitant Primary Lung Cancer and Metastatic Pulmonary Colorectal Cancer that Responded to Gemcitabine/Cisplatin/Bevacizumab Combination Therapy - 陳鴻明(Hung-Ming Chen); 潘競成(Chin-Chen Pan); 蔡俊明(Chun-Ming Tsai); 許文虎(Wen-Hu Hsu); 楊純豪(Shung-Haur Yang); 顏厥全(Chueh-Chuan Yen) (Journal of cancer research and practice, 2015)
Abstract The incidence of double primary malignancy in colorectal cancer is rare (approximately 1-6%), and synchronous double primary malignancy is even rarer for cases involving colorectal cancer. Indeed, its incidence is estimated to be less than 1%. The probability of concurrent colorectal cancer and lung cancer, in particular, is extremely low (approximately 0.1%). In this report, we present such a case of synchronous primary lung cancer and pulmonary metastatic colorectal cancer, which was mistaken for primary lung cancer with lung-to-lung metastasis. Tumors were identified in the upper and lower lobes of right lung. After the patient received a lung cancer chemotherapy, gemcitabine/cisplatin/bevacizumab, the right upper lobe tumor was stable in size, and the right lower lobe tumor regressed. Surprisingly, the right lower lobe tumor was proven to be metastatic colorectal cancer after surgical resection. A primary rectal tumor was then identified through colonoscopy. Subsequently, the patient underwent surgical resection of the primary rectal cancer and chemotherapy. She has now remained disease-free for more than two years.